Antifungal Secondary Metabolites Produced by the Fungal Endophytes: Chemical Diversity and Potential Use in the Development of Biopesticides - Xu, Kuo; Li, Xiu-Qi; Zhao, Dong-Lin; Zhang, Peng (Frontiers in Microbiology, 2021)
Plant diseases caused by phytopathogenic fungi can lead to huge losses in the agricultural fields and therefore remain a continuous threat to the global food security. Chemical-based fungicides contributed significantly in securing crop production. However, indiscriminate application of fungicides has led to increased chemical resistance and potential risks to human health and environment. Thus, there is an urgent need for searching for new bioactive natural products and developing them into new biopesticides. Fungal endophytes, microorganisms that reside in the fresh tissues of living plants, are regarded as untapped sources of novel natural products for exploitation in agriculture and/or medicine. Chemical examination of endophytic fungi has yielded enormous antifungal natural products with potential use in the development of biopesticides. This review summarizes a total of 132 antifungal metabolites isolated from fungal endophytes in the past two decades. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant antifungal properties. Moreover, some “star molecules”, such as griseofulvin and trichothecene, as well as their synthetic derivatives that possess high potential as candidates of new natural fungicides, are also presented herein.